Development of heat-treated chicken sausage enriched with Chlorella sorokiniana biomass - Fusio, Jadess Lorraine Z (2024.)
The present study aimed to develop. chicken sausage enriched with varying levels of Chlorella sorokiniana biomass and to investigate its nutritional and quality characteristics. Proximate, physicochemical, bioactive, and sensory properties, as well as consumer willingness-to-pay, and cost analysis of the sausages were evaluated. The incorporation of 1% to 3% (w/w) C. sorokiniana biomass significantly increased the crude protein, fat, and fiber contents of sausage treatments (p < 0.05). Chemical composition such as pH, aw, and water holding capacities were not significantly affected with the addition of the microalga biomass. Due to the presence of pigments in the microalga, color parameters were altered significantly resulting in a decrease in lightness (L*) and redness (a*), and an increase in yellowness (b*) values in the sausage formulation. Textural parameters such as hardness, adhesiveness, springiness, gumminess, and chewiness were significantly different compared to the control. However, the cohesiveness values of the sausage were not altered by the addition of the biomass (p < 0.05). Furthermore, chicken sausage with C. sorokiniana biomass increased the total phenolic and flavonoid contents of the sausages and showed significantly higher %DPPH Inhibition relative to the control sample without microalgae (p < 0.05). Likewise, the sensory analysis revealed that the biomass contributed significant effects on its aroma, taste, flavor, texture, and general acceptability. Sausage with 1% (w/w of C. sorokiniana biomass had the highest general acceptability with better sensory attributes and was thus considered the most acceptable sausage. Likewise, the study found that 85% of the surveyed consumers were willing to buy chicken sausage enriched with C. sorokiniana biomass and the estimated cost ranged from â‚± 139 to â‚± 167 for 1 1-kg pack. This research highlight the potential of adding C. sorokiniana biomass to enrich the nutritional content of meat products and satisfy consumer demand for sustainable and healthier food options.
Thesis (M.S. Food Science) -- [Miagao, Iloilo] : University of the Philippines Visayas, July 2024.